2005
DOI: 10.1073/pnas.0408238102
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the PhoP regulatory network of Escherichia coli and Salmonella enterica

Abstract: Genetic and genomic approaches have been successfully used to assign genes to distinct regulatory networks. However, the present challenge of distinguishing differentially regulated genes within a network is particularly hard because members of a given network tend to have similar regulatory features. We have addressed this challenge by developing a method, termed Gene Promoter Scan, that discriminates coregulated promoters by simultaneously considering both multiple cis promoter features and gene expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
239
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 195 publications
(250 citation statements)
references
References 42 publications
(42 reference statements)
10
239
1
Order By: Relevance
“…The PhoP protein is a DNA-binding transcriptional regulator (33,45) that increases RpoS levels indirectly because inactivation of the phoP gene had no effect on rpoS transcription. In Salmonella, PhoP increases RpoS levels by promoting transcription of the iraP (i.e., yaiB) gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PhoP protein is a DNA-binding transcriptional regulator (33,45) that increases RpoS levels indirectly because inactivation of the phoP gene had no effect on rpoS transcription. In Salmonella, PhoP increases RpoS levels by promoting transcription of the iraP (i.e., yaiB) gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor protein PhoQ responds to low Mg 2ϩ by promoting phosphorylation of the response regulator PhoP (28)(29)(30)(31), which binds to its target promoters to stimulate transcription of PhoP-activated genes (24,32). The Salmonella PhoP͞PhoQ system controls expression of Ϸ3% of the genome (33).…”
mentioning
confidence: 99%
“…First, a comparison with previously reported Salmonella PhoP-regulated promoters (Fig. 3A) (23,26) revealed that the sequence of the PhoP-binding motif is similar in Salmonella and Yersinia (Fig. S5).…”
Section: Promoter Architecture Dictates the Ability Of The Salmonellamentioning
confidence: 99%
“…We began by investigating Yersinia's ability to promote transcription of the S. enterica mgtA and ugtL genes, which have no orthologs in Y. pestis and harbor distinct promoter architectures (Fig. 1A) (21)(22)(23). Y. pestis produced fluorescence levels similar to those of S. enterica when transcription of a promoterless gfp gene was driven by the promoter of the mgtA gene (Fig.…”
Section: Differential Ability Of the Yersinia Phop Protein To Expressmentioning
confidence: 99%
“…[The latter genes harbor prototypical PhoP-dependent promoters (13)(14)(15)(16) such as that corresponding to the mgtA gene, which does not require proteins other than PhoP and RNA polymerase for in vitro transcription (ref. 17; J. C. Perez and E.A.G., unpublished data).…”
Section: Pmra-activated Genes Are Induced To Higher Levels Than Thosementioning
confidence: 99%